2019
DOI: 10.1177/1758573219831662
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of all suture fixation with tension band wiring and plate fixation of the olecranon

Abstract: Background Tension band wiring and plate fixation are common techniques used to stabilize simple olecranon fractures and osteotomies of the olecranon. All suture fixation is an alternative technique but has not been compared previously to these traditional methods. The aim of this study was to compare the clinical and radiographic outcomes of the three techniques. Methods One hundred and sixty-eight consecutive Mayo type 1 and 2 olecranon fractures (n = 138) and olecranon osteotomies (n = 30) with a minimum f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 16 publications
0
11
0
Order By: Relevance
“…The SR group had 2 complications after olecranon osteotomy, 1 radiological nonunion not requiring further surgery, and 1 failed fix-ation. None of the patients had suture irritation 97 . Currently, there is a multicentered RCT in the United Kingdom comparing SR with TBW called the Simple Olecranon Fracture Fixation Trial.…”
Section: Plate Osteosynthesismentioning
confidence: 92%
“…The SR group had 2 complications after olecranon osteotomy, 1 radiological nonunion not requiring further surgery, and 1 failed fix-ation. None of the patients had suture irritation 97 . Currently, there is a multicentered RCT in the United Kingdom comparing SR with TBW called the Simple Olecranon Fracture Fixation Trial.…”
Section: Plate Osteosynthesismentioning
confidence: 92%
“…TBS is theorised to decrease the need for hardware removal due to lack of a metal tension band implant [31]. The one included study comparing TBW and TBS supported this by demonstrating a 12.1% lower rate of hardware removal in TBS (p=0.217).…”
Section: Complicationsmentioning
confidence: 93%
“…al. which reported a significantly lower rate of reoperation in TBS when compared with TBS (p=0.002), with the need for revision fixation not Studies discussed but not included due to lack of statistical analysis.being reported in any TBS patients[31]. This study was not included due to a lack of separate analysis of patients with comminuted and non-comminuted fractures.…”
mentioning
confidence: 97%
“…a further recent comparative study has also reported on 89 patients treated with tBW, 38 patients treated with a plate, and 41 patients treated with tension suture fixation. 11 this study included a mix of olecranon fractures (n = 138) and olecranon osteotomies (n = 30). the reoperation rate for symptomatic implants was 36% for the tBW group, 11% for the plate group, and 0% for the suture fixation group.…”
Section: Management: Other Fixation Techniquesmentioning
confidence: 99%
“…tension-band wiring (tBW) has become a widely used fixation method for simple transverse displaced fractures with a stable elbow joint, with plating and suture fixation becoming increasingly popular alternative options. 1,[3][4][5][6]11 Plate fixation is considered superior in multifragmentary injuries, distal fractures and unstable injury patterns, fracture-dislocations, and/or osteoporotic bone, as it provides improved fracture fixation and a lower rate of reoperation. 1,2,12,13 a direct comparison of tBW and plate fixation has been the focus of prospective randomized controlled trials (rcts), particularly for stable simple displaced transverse fractures.…”
Section: Introductionmentioning
confidence: 99%